Increasing the Ability of Concentration Through the Implementation of Brain Gym - Septian, Rendra; Darajat, Jajat; Suntoda, Andi; Mulana, Mulana (Prodi PGSD Penjas FPOK UPI, 2018)
The purpose of this study is to improve the ability of concentration. Subjects in this study are the students of grade IV - VI Ciparay Elementary School 07 Kabupaten Bandung Sampling technique in this study is Purposive Sampling with a subject of 42 people. The method used in this study is the experimental method with One-Group Pretest-Posttest Design research. Measuring instrument in this study using Concentration Grid Exercise test. t paired test results. The obtained p-value value 0.00 0.05 Ho rejected, with an increase of 30% then there is the influence of the application of the gym gym to increase the ability of concentration in the students SDN Ciparay 07 Kab. Bandung.Â